Elderly Mobility: Demographic and Spatial Analysis of Trip Making in the Hamilton CMA, Canada - Páez, Antonio; Scott, Darren; Potoglou, Dimitris; Kanaroglou, Pavlos; Newbold, K. Bruce (Urban studies (Edinburgh, Scotland), 2007)
Recent interest in the urban transport challenges posed by the demographic outlook of ageing societies has prompted a growing body of scholarship on the subject. The focus of this paper is on the topic of elderly trip generation and the development of models to help formalise some important relationships between trip-making behaviour and personal, household and contextual variables (such as location). The case study is the Hamilton Metropolitan Area—an important functional component of Greater Toronto, itself one of the regions in Canada where the impact of ageing is expected to be most strongly felt. Using data from Toronto's Transport Tomorrow Survey and mixed ordered probit models, the study investigates the question of spatial and demographic variability in trip-making behaviour. The results support the proposition that tripmaking propensity decreases with age. However, it is also found that this behaviour is not spatially homogeneous and in fact exhibits a large degree of variability—a finding that highlights both the challenges of planning transport for the elderly and the potential of spatial analytical approaches to improve transport modelling practice.